Optimizing Digital Technology in Progressive Islamic Education to Enhance Public Literacy and Combat Hoaxes - Putra, Dhandy Hananthiyo Ardhy; Ayyaisy, Hanif In’am (Multicultural Islamic Education Review, 2025)
The proliferation of religious-based hoaxes in digital spaces poses a significant challenge to social cohesion and public literacy among Muslim communities. Inadequate digital literacy, particularly the lack of critical and ethical engagement with online content, contributes to the widespread dissemination of unverified information. This study examines the implementation of Tabayyun.id, a digital platform that integrates Islamic values—particularly the principle of tabayyun (information verification)—as a strategic approach to enhancing digital literacy among Muslims. Employing a qualitative case study method, the research involved website observation, document analysis, and in-depth interviews with developers, religious leaders, and active users. The study focuses on how the platform’s key features—news verification tools, educational articles, and Islamic discussion forums—contribute to shaping user behavior and promoting ethical digital practices. Findings reveal a significant behavioral shift among users, with the rate of information verification increasing from 45% to 85% after engaging with the platform. The forum component also fosters collaborative learning and strengthens digital ukhuwah (brotherhood), with over 500 new threads monthly and high user satisfaction. Despite technical and social challenges such as limited access and digital illiteracy in certain demographics, the platform demonstrates strong potential for broader educational impact. The study concludes that value-based digital platforms like Tabayyun.id can serve as effective tools in progressive Islamic education, offering a model for integrating spiritual values with digital competencies in combating misinformation.